Desde
$\begin{array}\\
\frac1{k}
&> \int_k^{k+1} \frac{dx}{x}
> \frac1{k+1}\\
\sum_{k=n+1}^{2n}\frac1{k}
& > \sum_{k=n+1}^{2n}\int_k^{k+1} \frac{dx}{x}
> \sum_{k=n+1}^{2n}\frac1{k+1}\\
or\\
\sum_{k=n+1}^{2n}\frac1{k}
& > \int_{n+1}^{2n+1} \frac{dx}{x}
> \sum_{k=n+1}^{2n}\frac1{k}-\frac1{n+1}+\frac1{2n+1}\\
\end{array}
$
Desde
$\int_{n+1}^{2n+1} \frac{dx}{x}
=\ln(2n+1)-\ln(n+1)
=\ln(2-\frac1{n+1})
=\ln(2)-\ln(1-\frac1{2n+2})
$,
si
$d(n)
=\ln(2)-\sum_{k=n+1}^{2n}\frac1{k}
$,
$d(n)
< \ln(1-\frac1{2n+2})
< 0
$
y
$d(n)
>\ln(1-\frac1{2n+2})-\frac1{n+1}+\frac1{2n+1}
$.
Configuración
$k=2n+1$
en
$\frac1{k}
> \int_k^{k+1} \frac{dx}{x}
> \frac1{k+1}
$
tenemos
$\frac1{2n+1}
> -\ln(1-\frac1{2n+1})
> \frac1{2n+2}
$.
Por lo tanto
$d(n)
>-\frac1{2n+1}-\frac1{n+1}+\frac1{2n+1}
=-\frac1{n+1}
$.
así
$$-\frac1{n+1}
< \ln(2)-\sum_{k=n+1}^{2n}\frac1{k}
< 0.
$$